Influence of thymoxamine on changes in pupil diameter and accommodation produced by homatropine and ephedrine. Issue 2 (February 1976) - Small, S.; Stewart-Jones, J. H.
Abstract : Local instillation of thymoxamine eye drops (0-1%) completely reversed the mydriasis produced by ephedrine (5%) but not that produced by ephedrine (5%) together with homatropine (0-5%). Small but significant changes in accomodation were found with ephedrine and with thymoxamine, as well as the larger expected changes with homatropine.